2017
DOI: 10.1371/journal.pone.0172309
|View full text |Cite
|
Sign up to set email alerts
|

Brugia malayi microfilariae transport alphaviruses across the mosquito midgut

Abstract: Concurrent ingestion of microfilariae (MF) and arboviruses by mosquitoes can enhance mosquito transmission of virus compared to when virus is ingested alone. Within hours of being ingested, MF penetrate the mosquito midgut and introduce virus into mosquito hemocoel, creating a disseminated viral infection much sooner than normal. How virus is actually introduced is not known. In this report, we present experimental evidence that suggests that certain alphaviruses may adhere or otherwise associate with sheathed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Evidence to date indicates that the presence of parasites such as microfilarial nematodes is likely to be of greater importance than the presence of other arboviruses in a bloodmeal, with studies of simultaneous co-ingestion of multiple arboviruses resulting in similar levels of infection, dissemination and transmission to those seen during single-virus studies [ 70 ], suggesting that considering each virus in isolation for epidemiological purposes may be entirely valid. However, several studies have shown that simultaneous ingestion of an arbovirus and a nematode may result in elevated susceptibility to the arbovirus [ 71 , 72 , 73 ], initially assumed to be a result of the mechanical damage to the gut caused by the microfilariae allowing the virus to bypass the midgut infection and escape barriers in a similar way to intrathoracic inoculation, although more recent evidence has suggested that certain arboviruses may specifically adhere to the microfilariae and be actively transported within the insect [ 74 ]. Simulation studies suggest that this interaction could result in macro-scale epidemiological differences in outbreak frequency [ 75 ].…”
Section: Methods Of Infectionmentioning
confidence: 99%
“…Evidence to date indicates that the presence of parasites such as microfilarial nematodes is likely to be of greater importance than the presence of other arboviruses in a bloodmeal, with studies of simultaneous co-ingestion of multiple arboviruses resulting in similar levels of infection, dissemination and transmission to those seen during single-virus studies [ 70 ], suggesting that considering each virus in isolation for epidemiological purposes may be entirely valid. However, several studies have shown that simultaneous ingestion of an arbovirus and a nematode may result in elevated susceptibility to the arbovirus [ 71 , 72 , 73 ], initially assumed to be a result of the mechanical damage to the gut caused by the microfilariae allowing the virus to bypass the midgut infection and escape barriers in a similar way to intrathoracic inoculation, although more recent evidence has suggested that certain arboviruses may specifically adhere to the microfilariae and be actively transported within the insect [ 74 ]. Simulation studies suggest that this interaction could result in macro-scale epidemiological differences in outbreak frequency [ 75 ].…”
Section: Methods Of Infectionmentioning
confidence: 99%
“…Laboratory research has shown that arboviral transmission is enhanced in haematophagous insects, such as mosquitoes, that concurrently ingest microfilariae (Vaughan and Turell, 1996;Vaughan et al, 1999). It has been shown that microfilariae penetrating the mosquito midgut may introduce viruses to the hemocoel if coinfected, resulting in dissemination and enhanced transmission (Vaughan et al, 2007;Vaughan and Turell, 2017). This phenomenon, known as 'microfilarial enhancement of arboviral transmission' (Vaughan and Turell, 2017), has not been investigated in blackflies.…”
Section: Research Updatementioning
confidence: 99%
“…Mosquitoes are frequently infected with parasites that may play a role in alphavirus-mosquito interactions [ 39 ]. Microfilariae are an early developmental stage of certain parasites which are known to live in vertebrates.…”
Section: The Roles Of Parasites In Alphavirus Infectionmentioning
confidence: 99%
“…This facilitation of viruses across the midgut barrier is known as microfilarial enhancement of arboviral transmission. It is hypothesised that this results in greater vector competence, as less susceptible mosquitoes are infected by viruses, increasing the number of infected mosquito vectors during a transmission cycle [ 39 ]. Additionally, the shorter virus incubation period allows the virus to be transmitted by the mosquitoes quickly, leading to enhanced arboviral transmission [ 39 ].…”
Section: The Roles Of Parasites In Alphavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation